2012
DOI: 10.1089/apc.2011.0277
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Serologic Survey of Men Who Have Sex with Men in Beijing, China: Implication for HIV Intervention

Abstract: We assessed HIV prevalence and associated behaviors and risk factors among men who have sex with men (MSM) in Beijing, China. Five hundred MSM were recruited for a biological and behavioral survey using respondent-driven sampling (RDS) in 2009. Serologic specimens were tested for markers of HIV and syphilis infection. A computer-assisted personal interview (CAPI) administered questionnaire gathered information including demographic characteristics, sexual behaviors, HIV testing, and social norms concerning con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 47 publications
6
37
1
1
Order By: Relevance
“…In addition, enrolled subjects may visit other clinics for STD treatments, lowering the estimated STD incidence. Nevertheless, the STD rate reported here is similar to that reported in previous studies, 12,14,15,21,24,25,42,43 and represents the current scenario in Taiwan.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, enrolled subjects may visit other clinics for STD treatments, lowering the estimated STD incidence. Nevertheless, the STD rate reported here is similar to that reported in previous studies, 12,14,15,21,24,25,42,43 and represents the current scenario in Taiwan.…”
Section: Discussionsupporting
confidence: 90%
“…Fan and associates 24 reported that HIV infection was associated with syphilis among MSM in Beijing, China, and that syphilis control strategies such as changing social norms about condom use may have an impact on HIV prevention. 24 Liao and colleagues 25 noted that targeting the highly prevalent bisexual behavior with multiple sexual partners and unprotected sex in Shandong's gay community may have an influence on HIV transmission. 25 Ko and associates 21 also highlighted that 1 year after enrollment into the CM program in Tainan, Taiwan, 80% of the HIVpositive patients practiced safe sex.…”
Section: Discussionmentioning
confidence: 99%
“…In the bivariate analysis, the use of any illicit drug in the past 12 months was a predictive variable for syphilis and is in agreement with other published studies (FAN et al, 2012;PAN et al, 2013;OTIENO et al, 2014). On the other hand, in multivariate analysis, only the realization of circumcision was considered statistically significant as a protective factor for syphilis.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have demonstrated differences in the characteristics mentioned above in the studied populations (GUO et al, 2011;PAN et al, 2013). By another hand, in this study, the majority of attended individuals is not married, have had the first sexual relation with less than 16 years, has multiple partners and does not use condoms, these are common features in epidemiological studies of sexually transmitted diseases (FAN et al, 2012;OTIENO et al, 2014).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation